Analysis of Moisture Distribution and Key Volatile Flavor Compounds in Prepared Grilled Fish - Yan ZHANG; Shengkai WANG; Xun FU; Tingting FENG; Xiang LI; Qingyu NIE (Shipin gongye ke-ji, 2024)
With the ready-to-heat prepared grilled fish as study subject, the moisture distribution and volatile flavor compounds of grilled fish under different electric grilling conditions were investigated by LF-NMR and HS-SPME-GC-MS detection technology. The results showed that the lowest processing loss and the highest water holding capacity were found in the grilled fish baked at 250 °C for 20 min. The main form of water in grilled fish was non-flowable water, with the lowest relaxation times T22 and T23 for grilled fish at 200 °C, followed by grilled fish at 250 °C. The T2 inversion spectrum shifted to the left overall, indicating that the degree of freedom of water molecules decreased. Grilled fish at 250 °C for 20 min had the highest percentage of peak area of non-flowable water (A22) that up to 94.03%, and had the lowest percentage of peak area of free water (A23) as low as 1.93%, indicating that muscle tissue hold water better. A total of 70 volatile compounds were identified in five groups of grilled fish, including aldehydes, ketones, alcohols and hydrocarbons. The key volatile flavor compounds were screened by their relative odor activity values as 12, 9, 11, 8 and 8, respectively. The flavor compounds that contributed significantly to the five groups of samples were hexanal, 1-octen-3-ol and nonanal, with guaiacol and 4-methylphenol being the key flavor compounds specific to charcoal grilled fish. The key volatile flavor compounds of grilled fish baked under different conditions differed significantly by principal component analysis. Correlation analysis showed that A22 was significant positively correlated with isovaleraldehyde, heptanal and 2,3-octanedione (P<0.05) and significant negatively correlated with nonanal and guaiacol (P<0.05). The results of this study would provide a reference for the development of prepared grilled fish.